Analisis faktor-faktor yang mempengaruhi bid-ask spread saham pada perusahaan yang tergabung dalam indeks LQ45 periode 2013 - 2016 - Kamat Apriyanto; F. Defung; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
This study aims to determine the effect of stock price, stock trading volume, stock return volatility, and stock trading frequency on bid-ask spread. This study uses purposive sampling method, the population is the corporations which listed in LQ45 Index from 2013 to 2016. There are 24 corporations as samples use in this study. The analysis of this study used Multiple Linear Regression. Results from t-test explains that the stock price does not affect the bid-ask spread with p-value significant 0.342. The stock trading volume has a positive and significant effect on bid ask spread with p-value significant 0.000. Stock return volatility has a positive and significant effect on bid ask spread with p-value significant 0,000. Stock frequency trading has a negative and significant effect on the bid-ask spread with a p-value significant 0.000. Simultaneously (F-test) shows that stock price, stock trading volume, stock return volatility, and stock trading frequency of stock have significant effect to bid ask spread with p-value 0,000.